Precise study of hyperfine structure in the 23P state of He3 - Prestage,JD; Johnson,CE; Hinds,EA; Pichanick,FMJ (Physical Review A, 1985)
The optical-microwave atomic-beam magnetic resonance technique has been used to measure four hyperfine transitions in the 23P state He3. These were used to determine the three hyperfine interaction constants (in MHz) as follows: contact, C=-4283.84-0.01+0.02; nuclear-moment-electron-orbit, D=-28.060.06; nuclear-moment-electron-momment, E=+7.100.02. THe results, which are in excellent agreement with theory, give a clear indication of the effects of core polarization on the hyperfine structure. We conclude that to the accuracy indicated the structure of the 2 3P state, including mass-dependet and quantum electrodynamic corrections to the fine structure, and relativistic and core-polarization corrections to the hyperfine structure, is well understood. © 1985 The American Physical Society.